A comprehensive study of Interatomic Coulombic Decay in argon dimers: extracting R-dependent absolute decay rates from the experiment - Rist, Jonas; Miteva, Tsveta; Gokhberg, Kirill (Chemical physics, 2017)
In this work we present a comprehensive and detailed study of Interatomic Coulombic Decay (ICD) occurring after irradiating argon dimers with XUV-synchrotron radiation. A manifold of different decay channels is observed and the corresponding initial and final states are assigned. Additionally, the effect of nuclear dynamics on the ICD electron spectrum is examined for one specific decay channel. The internuclear distance-dependent width Γ(R) of the decay is obtained from the measured kinetic energy release distribution of the ions employing a classical nuclear dynamics model.
Available online 15 September 2016
Gesehen am 27.06.2018